Airflow obstruction, impaired lung function and risk of sudden cardiac death: a prospective cohort study. Issue 7 (20th August 2021) - Cheng, Yun-Jiu; Chen, Zhen-Guang; Yao, Feng-Juan; Liu, Li-Juan; Zhang, Ming; Wu, Su-Hua
Abstract : Background: Growing evidence suggests that compromised lung health may be linked to cardiovascular disease. However, little is known about its association with sudden cardiac death (SCD). Objectives: We aimed to assess the link between impaired lung function, airflow obstruction and risk of SCD by race and gender in four US communities. Methods: A total of 14 708 Atherosclerosis Risk in Communities (ARIC) study participants who underwent spirometry and were asked about lung health (1987–1989) were followed. The main outcome was physician-adjudicated SCD. Fine-Gray proportional subdistribution hazard models with Firth's penalised partial likelihood correction were used to estimate the HRs. Results: Over a median follow-up of 25.4 years, 706 (4.8%) subjects experienced SCD. The incidence of SCD was inversely associated with FEV1 in each of the four race and gender groups and across all smoking status categories. After adjusting for multiple measured confounders, HRs of SCD comparing the lowest with the highest quintile of FEV1 were 2.62 (95% CI 1.62 to 4.26) for white males, 1.80 (95% CI 1.03 to 3.15) for white females, 2.07 (95% CI 1.05 to 4.11) for black males and 2.62 (95% CI 1.21 to 5.65) for black females. The above associations were consistently observed among the never smokers. Moderate to very severe airflow obstruction was associated with increased risk of SCD. Addition of FEV1 significantly improved the predictive power for SCD. Conclusions: Impaired lung function and airflow obstruction were associated with increased risk of SCD in general population. Additional research to elucidate the underlying mechanisms is warranted.